2014
DOI: 10.1128/aem.02414-13
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Gull Fecal Microbial Community Reveals the Dominance of Catellicoccus marimammalium in Relation to Culturable Enterococci

Abstract: Gulls are prevalent in beach environments and can be a major source of fecal contamination. Gulls have been shown to harbor a high abundance of fecal indicator bacteria (FIB), such as Escherichia coli and enterococci, which can be readily detected as part of routine beach monitoring. Despite the ubiquitous presence of gull fecal material in beach environments, the associated microbial community is relatively poorly characterized. We generated comprehensive microbial community profiles of gull fecal samples usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…The Gull2 marker was much more consistent and, on average, was four orders of magnitude higher than FIB. Next-generation sequencing has revealed that Catellicoccus is the most abundant genus in gull feces, representing, on average, 55% of the total community, which illustrates the utility of Catellicoccus marker assays to detect gull waste (43). The same study showed that Enterococcus spp.…”
Section: Discussionmentioning
confidence: 52%
“…The Gull2 marker was much more consistent and, on average, was four orders of magnitude higher than FIB. Next-generation sequencing has revealed that Catellicoccus is the most abundant genus in gull feces, representing, on average, 55% of the total community, which illustrates the utility of Catellicoccus marker assays to detect gull waste (43). The same study showed that Enterococcus spp.…”
Section: Discussionmentioning
confidence: 52%
“…Gulls, other shorebirds and waterfowl are suspect fecal pollution sources at many beaches. Gulls appear to harbor very different fecal microbial communities than humans, one that is dominated by enterococci and E. coli , with a limited number of fecal anaerobes [27, 112, 113]. Based on cloning of the microbial community, a genetic marker targeting Catellicoccus marimammalium was described by Lu and colleagues [112].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Based on cloning of the microbial community, a genetic marker targeting Catellicoccus marimammalium was described by Lu and colleagues [112]. Deep sequencing demonstrated this organism was the dominant community member (in some cases comprising >90% of the total community) in gull feces and much more abundant then traditional enterococci fecal indicators [113]. Comparison with sewage samples that were also deeply sequenced [100] suggested this target was completely absent in sewage and therefore potentially a reliable marker to complement sewage indictors at beaches.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…To assess the levels of E. coli and enterococcus reads in our community sequences, we used the SRA BLAST tool. We performed a BLAST of the community sequences from the present study (SRP052297) against 16S sequences of enterococci (accession numbers KF250762 to KF250872) (34) and E. coli (X80724) obtained from GenBank.…”
Section: Methodsmentioning
confidence: 99%